Nature-based solutions (Nbs) for flood mitigation: Recent UK case studies - Rameshwaran Ponnambalam; Blake James; Trill Emily; Robotham John; Bishop James; Old Gareth; O’Brien Alex; Scarlett Pete (E3S Web of Conferences)
Implementing Nature-based solutions (Nbs) can potentially reduce the flood risk in catchments and improve water and soil quality and biodiversity. Understanding the hydrological functioning of the Nbs interventions is important in determining their effectiveness in reducing flood risks. This study reports the findings from two UK projects namely the Littlestock Brook Natural Flood Management (NFM) pilot and LANDWISE (Land Management in Lowland Catchments for Integrated Flood Risk Reduction). The Littlestock Brook NFM study showed that the Nbs interventions successfully attenuated all storm event discharge peaks during the monitoring period (up to 55% reductions) and that over 40% of the total storage volume remained available throughout all events. The LANDWISE project demonstrated that whilst increased organic matter improves soil structure and porosity, innovative arable management practices (e.g., controlled traffic and min till) can also improve soil structure and porosity, increasing soil hydraulic conductivity and therefore NFM potential.